INVESTIGATION OF THE MICROTEK SCANMAKER 1000XL PLUS SCANNER OF THE INSTITUTE OF ASTROPHYSICS OF THE ACADEMY OF SCIENCES OF THE REPUBLIC OF TAJIKISTAN - Mullo-Abdolov, A.; Kokhirova, G.; Relke, H.; Yuldoshev, Q.; Protsyuk, Yu.; Andruk, V. (Одеські астрономічні публікації, 2017)
This work was done to estimate the accuracy of the processing method of photographic plates and the detailed study of the Microtek ScanMaker 1000XL Plus scanner, which plans to be used for the digitizing of about 1600 photographic plates of the Astrophysics Institute of the Academy of Sciences of the Republic of Tajikistan (Dushanbe) recorded for the FON project. For the processing of these photographic plates will be used software created in the LINUX/MIDAS/ROMAFOT environment. Six sequential scans of a single plate (1150, the Pleiades cluster) with a spatial resolution of 1200 dpi were processed to evaluate the repeatability of the scanner’s astrometric and photometric errors. The size of photographic plates is 8 x 8 degrees (30 x 30 cm or 13000 x 13000 pixels). The estimated errors of the scanner for the stars brighter than B < 13.5m are σxy = ± 0.054 pixels for the rectangular coordinates and σm = ± 0.020m for the instrumental magnitudes. The estimated astrometric accuracy of the processing of stellar fields of photographic plates in the system of the Tycho-2 catalogue is σαδ = ± 0.13".